Frecuencia de fertiriego con lixiviado de humus en el rendimiento del forraje Panicum maximum cultivar tanzania bajo sistema de aspersión en Zungarococha, Loreto. 2023 - Pizango Asipali, Domenico (2024)
Sprinkler systems with foliar biofertilizers in the tropical humid zone are not very common due to the high rainfall there is. The title of this research work is “FREQUENCY OF FERTIGATING WITH HUMUS LEACHING IN THE YIELD OF FORAGE Panicum maximum CULTIVATING TANZANIA UNDER A SPRINKLER SYSTEM IN ZUNGAROCOCHA, LORETO. 2023”With a Complete Random Block Design (D.B.C.A), with four treatments and four repetitions and experimental units of 4 m x 4 m, the treatments under study are T0 (control), T1 (sprinkler system with worm castings every 2 days), T2 ((sprinkler system with worm castings every 4 days) and T3 ((sprinkler system with worm castings every 6 days), giving the following information: that treatment T1 (sprinkler irrigation every 2 days with worm humus leachate) exceeded the dependent variables of plant height of 1.48 meters, green matter of 3.24 kg/m2 and dry matter of 0.65 kg/m2, coverage of 92.88 percent, this with a time of 60 days from the beginning From the sowing yield of the T1 treatment (sprinkler irrigation every 2 days with worm humus leachate) we have a plot of 51.68 kilos /16 square meters and 32,300 kilos/hectare.